TREND IN UTILIZATION OF MOBILE HEALTH SERVICES, MORBIDITY PATTERN & HEALTH SEEKING IN UTTARAKHAND - Roy, Debabrata; Kakkar, Rakesh; Kandpal, S D (Indian Journal of Community Health, 2012)
Introduction: Mobile Health services is unique approach and are being offered to the community living in far-flung, difficult mountainous outreaches in a bid to supplement the existing public health facilities with the aim of providing minimum basic primary health care. Objective: To provide quality diagnostic & curative care through mobile health clinics at select mountainous outreaches of Uttarakhand state & impart basic health education and community based sensitization towards preventive and promotive health and hygiene through community endorsed Behaviour Change Communication (BCC). Methodology: Prior to service delivery Community Needs Assessment was done. A movement & operational plan was formulated in which a team of service providers from various specialities and supporting staff was recruited. The team provided 10 days' extensive bimonthly mobile health services on a `fixed day, fixed time and fixed place' schedule along pre-designated service locations across the three districts Data generated during Ist implementation quarter i.e. March-May 2007 was assumed as baseline for the trend in utilization of mobile health services, morbidity pattern & health seeking in Uttarakhand. Generated data was collated and analysed in the Department of Community Medicine, HIHT. Result: Data analysed show that in terms of trend in utilization of mobile health services, 27723 clients sought mobile health services during the period & central tendency was 3465 (12.5%) as against baseline of 4899 (17.7%) clients. Mean of clients seeking mobile health services for key morbidities was highest for Musculoskeletal disorders i.e. 790 (22.8%) followed by clients with Gastrointestinal (GI) disorders i.e. 688 (19.8%), Genitourinary system disorders i.e. 621(17.9%) and Respiratory system disorders i.e.286 (8.2%).Average number of clients provided investigative facilities in all the 8 quarters were 3465 out of which majority was investigated in laboratory (70.6%) for haemogram & urogram including blood glucose estimation followed by Ultrasound (13.2%), X-ray (10.8%) and ECG (1%). Provision of mobile health services has certainly increased the outreach of health care services to the hitherto underserved & unserved regions of the state.